2013
DOI: 10.5897/ajb11.3952
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of ciprofloxacin resistance in Shigella dysenteriae

Abstract: Bacterial resistance to quinolones has emerged rapidly and such resistance has traditionally been attributed to the chromosomally mediated mechanisms that alter the quinolone targets and/or overproduce multidrug resistance efflux pumps. In the present investigation possible mechanism of ciprofloxacin (Cp) resistance in Shigella dysenteriae was studied. While the growth of sensitive S. dysenteriae was completely inhibited at 1 µg /ml concentration of ciprofloxacin, the resistant strain tolerated even 10 µg /ml … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 17 publications
0
0
1
Order By: Relevance
“…In case of Azithromycin, zone reduced from 24 to 18 mm at their MIC after 13 subcultures. Nilima Lankeshwar et al [22] studies in 2013 and found that the S. dysenteriae resistant strain showed resistant to 10 µg/ml concentration of ciprofloxacin with no zone of inhibition, whereas in our study, ZOI reduced to 15 mm from 22 mm at their MIC (20 µg/ml) after development of resistance. From microscopic view it was observed that sensitive strain of Shigella dysenteriae was comparatively large in size and rod in shape, but the resistant strains look small and oval, instead.…”
Section: Changes In Genome Level Ofcontrasting
confidence: 61%
“…In case of Azithromycin, zone reduced from 24 to 18 mm at their MIC after 13 subcultures. Nilima Lankeshwar et al [22] studies in 2013 and found that the S. dysenteriae resistant strain showed resistant to 10 µg/ml concentration of ciprofloxacin with no zone of inhibition, whereas in our study, ZOI reduced to 15 mm from 22 mm at their MIC (20 µg/ml) after development of resistance. From microscopic view it was observed that sensitive strain of Shigella dysenteriae was comparatively large in size and rod in shape, but the resistant strains look small and oval, instead.…”
Section: Changes In Genome Level Ofcontrasting
confidence: 61%